GE_GERICHTE C/8157/2018 vom 27. August 2019 - GE Cour de justice (2019)
PROTECTION DE L'UNION CONJUGALE;OBLIGATION D'ENTRETIEN;CONJOINT;ENFANT;REVENU HYPOTHÉTIQUE | CC.163; CC.176.al1.ch1; CC.173.al3; CC.276; CC.285.al1